Metode Pembelajaran Berbasis Masalah dalam Pendidikan Tinggi - Nurul Handini; Rizki Ramadhani; Tiara Ramadhani; Siti Fadilla; Annisa Ramadhani (Pusat Riset dan Inovasi Nasional, 2024)
The Problem-Based Learning (PBL) method is a popular approach in education that allows students to develop critical thinking and problem-solving skills through solving real problems. PBL involves steps such as problem identification, research, and presentation of solutions, with a focus on students learning independently and in small groups. Although PBL is effective in improving student learning outcomes, there are challenges such as the need for teachers who are skilled in guiding students and longer time to solve problems. Characteristics of PBL include student-centered learning, teachers as facilitators, and problems as learning stimuli. The PBL strategy emphasizes the importance of starting learning with problems that are relevant to students' real lives and gives students great responsibility in their own learning process. The research method in this study uses qualitative research methods. The method used is library research.